Communication problem at KTMB commuter / Norsaliha Abd Hadi, Ain Amalina Mat Zanggi and Azefa Ahmad - Abd Hadi, Norsaliha; Mat Zanggi, Ain Amalina; Ahmad, Azefa (2018)
KTMB commuters provide rail services around Kuala Lumpur and Klang Valley area. Because of problem with late train arrival, we would like to suggest KTMB to use their official Facebook page as main communicator tools to reach their customer. KTMB commuters should informed whenever there is disruption in train services, and also inform customer about alternative way for customers to continue their journey in their Facebook page. KTMB also can try to develop an application to make it easier for KTMB to communicate with customer.